A spherical resin hard carbon coating negative electrode sheet and a preparation method thereof, and a sodium-ion battery with few negative electrodes
Patent Information
- Application Number
- CN202611374557.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-13
AI Technical Summary
[0003]然而,现有技术中钠离子电池仍存在诸多技术瓶颈:第一,传统无负极路线中,裸铝箔表面钠成核势垒高、成核位点分布不均,导致钠枝晶不可控生长,首次库仑效率低于80%,循环衰减极快
本发明的负极片中,采用窄粒径分布的球形树脂硬碳,构建厚度为12~40μm的薄涂层。其中,球形树脂硬碳的曲率均一,能够在涂层表面形成均匀规整的成核位点阵列,硬碳自身贡献的储钠容量作为“底钠”,剩余容量由钠金属在涂层表面/内部孔隙中原位沉积补充,从而兼顾硬碳储钠与钠金属沉积双重功能。与现有薄涂层技术中碳颗粒分布宽、成核不均的问题相比,本发明显著改善了钠沉积的均匀性和可逆性。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of sodium-ion battery technology, specifically relating to a spherical resin hard carbon coated negative electrode sheet and its preparation method, and a sodium-ion battery with few negative electrodes. Background Technology
[0002] Sodium-ion batteries, due to the abundant and inexpensive availability of sodium resources, have become an important supplement to lithium-ion batteries. In recent years, anode-lean sodium-ion batteries have received widespread attention in the industry to improve their energy density. Anode-lean sodium-ion batteries refer to batteries where only an extremely thin layer of hard carbon active material (typically ≤40μm, with a much lower areal capacity than the positive electrode) is coated on the negative electrode side. During the first charge cycle, some sodium ions released from the positive electrode embed into the hard carbon layer, while the remainder are deposited in situ as metallic sodium on the surface / inside of the hard carbon layer. Compared to traditional thick-coated negative electrodes (50~100μm), the anode-lean structure significantly reduces the negative electrode mass ratio, thereby effectively improving the battery's energy density. Compared to bare current collectors without a negative electrode, the thin coating can provide an array of nucleation sites and a buffer framework, and significantly improve cycle stability.
[0003] However, existing sodium-ion batteries still face several technical bottlenecks: First, in the traditional anode-less approach, the high sodium nucleation barrier and uneven distribution of nucleation sites on the bare aluminum foil surface lead to uncontrolled sodium dendrite growth, resulting in an initial coulombic efficiency of less than 80% and extremely rapid cycle degradation. Second, in the traditional thick-coated anode approach, the hard carbon coating thickness is 50-100 μm, accounting for a large proportion of the anode mass, which weakens the cost advantage of sodium-ion batteries. Simultaneously, the thick coating has a longer ion transport path, limiting rate performance. Third, in existing thin-coated solutions with fewer anodes, the carbon particles used in conventional carbon-coated aluminum foil have a wide particle size distribution (D...). 50 The diameter is 5~15μm, D max Larger than 20 μm, irregular particle morphology, and large specific surface area (8~20 m²). 2 The coating uniformity and interface stability are insufficient, which severely restricts the battery cycle life and initial efficiency. Fourth, some existing modification solutions rely on special equipment such as plasma treatment, etching or vacuum deposition, which have poor compatibility with existing electrode production lines and are difficult to scale up.
[0004] Therefore, there is an urgent need to develop a negative electrode preparation technology that can simultaneously achieve the dual functions of hard carbon sodium storage and sodium metal deposition under thin coating conditions, while possessing a uniform nucleation site array, low interfacial side reactions, and process compatibility with existing production lines. Summary of the Invention
[0005] To overcome the shortcomings of existing technologies, the purpose of this invention is to provide a spherical resin hard carbon coated negative electrode sheet and its preparation method, as well as a low-negative-electrode sodium-ion battery. The negative electrode sheet of this invention is a low-negative-electrode sodium-ion battery negative electrode sheet characterized by a spherical resin hard carbon ultrathin coating. It constructs a uniform nucleation site array through narrow-diameter distributed spherical particles, combining the dual functions of hard carbon sodium storage and sodium metal deposition. It achieves an optimal balance between energy density, cycle life, and kinetic performance, and also possesses the advantages of high performance, low cost, and easy mass production. It can be widely used in the preparation of low-negative-electrode sodium-ion batteries, especially suitable for sodium-ion batteries with high energy density and long cycle life.
[0006] To achieve the above objectives, a first aspect of the present invention provides a spherical resin hard carbon coated negative electrode, comprising a current collector and an active material layer loaded on the surface of the current collector; the active material layer comprises spherical resin hard carbon; the thickness of the active material layer is 12~40μm; the spherical resin hard carbon is obtained by carbonization treatment of phenolic resin microspheres, and the median particle size D 50 The thickness is 2.0~3.0μm.
[0007] Further, the current collector is an aluminum alloy foil or aluminum foil; the thickness of the current collector is 8~15μm; the maximum particle size D of the spherical resin hard carbon is... max The particle size ranges from 5.8 to 7.8 μm, with a minimum particle size D. min Its thickness is 1.1~1.8μm, and its BET specific surface area is 1.9~3.1m². 2 / g; the phenolic resin microspheres are prepared by emulsion polymerization.
[0008] Furthermore, the raw materials for preparing the active material layer include, by mass parts: 90-96 parts of spherical hard carbon resin, 1-4 parts of conductive carbon black, 1-4 parts of sodium carboxymethyl cellulose, and 2-5 parts of styrene-butadiene rubber emulsion.
[0009] Further, the preparation method of the spherical resin hard carbon includes: heating phenol, formaldehyde aqueous solution, and polyvinyl alcohol in water under stirring conditions to obtain phenolic resin microspheres; carbonizing the phenolic resin microspheres in a protective atmosphere to obtain the spherical resin hard carbon; the mass ratio of phenol, formaldehyde aqueous solution, and polyvinyl alcohol is (80~120):(120~200):(2~5); the stirring speed is 200~500 rpm; the heating reaction temperature is 70~90℃ and the time is 2~8h; the carbonization treatment temperature is 1100~1300℃ and the time is 2~5h.
[0010] A second aspect of the present invention provides a method for preparing the above-mentioned spherical resin hard carbon coated negative electrode sheet, comprising the following steps: Spherical resin hard carbon, conductive carbon black, sodium carboxymethyl cellulose, styrene-butadiene rubber emulsion, and solvent are mixed evenly to obtain a coating slurry. The coating slurry is then coated onto the surface of the current collector, dried, and rolled to obtain the spherical resin hard carbon coated negative electrode sheet. The amount of spherical resin hard carbon used is 90-96 parts by mass, the amount of conductive carbon black is 1-4 parts, the amount of sodium carboxymethyl cellulose is 1-4 parts, and the amount of styrene-butadiene rubber emulsion is 2-5 parts.
[0011] Furthermore, the solvent is water; the solid content of the coating slurry is 30-40%.
[0012] Furthermore, the preparation steps of the coating slurry specifically include: first, dissolving sodium carboxymethyl cellulose in a solvent to prepare a glue solution; adding spherical resin hard carbon and conductive carbon black to the glue solution and stirring; finally adding styrene-butadiene rubber latex and stirring; then adding solvent and adjusting the solid content; finally stirring and degassing to obtain the coating slurry.
[0013] Furthermore, the coating speed is 1.0~5.0m / min, and the coating gap is 30~92μm; the drying adopts multi-stage hot air drying, the drying temperature is 60~120℃, and the total drying time is 3~6min; the rolling is carried out at room temperature, and the rolling linear pressure is 80~270N / mm.
[0014] A third aspect of the present invention provides a sodium-ion battery with a low negative electrode, comprising a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte, wherein the negative electrode is the aforementioned negative electrode or a negative electrode prepared by the aforementioned preparation method.
[0015] Further, the positive electrode sheet includes a positive current collector and a positive active material layer loaded on the surface of the positive current collector; the raw materials for preparing the positive active material layer include sodium nickel iron manganese oxide, conductive carbon black, and a binder; the non-aqueous electrolyte contains a sodium salt, a non-aqueous organic solvent, and fluoroethylene carbonate; the separator is a polypropylene or polyethylene separator. Further, the sodium salt is sodium hexafluorophosphate.
[0016] The technical solution of the present invention has the following beneficial effects: In the negative electrode of this invention, spherical resin hard carbon with a narrow particle size distribution is used to construct a thin coating with a thickness of 12-40 μm. The spherical resin hard carbon has uniform curvature, enabling it to form a uniform and regular array of nucleation sites on the coating surface. The sodium storage capacity contributed by the hard carbon itself serves as the "base sodium," while the remaining capacity is supplemented by in-situ deposition of sodium metal on the coating surface / inner pores, thus achieving the dual functions of hard carbon sodium storage and sodium metal deposition. Compared with the problems of wide carbon particle distribution and uneven nucleation in existing thin coating technologies, this invention significantly improves the uniformity and reversibility of sodium deposition.
[0017] This invention, through systematic experiments, discovered that a coating thickness of 12–40 μm, with spherical particles stacked in a few layers, ensures both sufficient nucleation site density and balanced ion transport efficiency and cycling performance. When the coating is too thin (e.g., 5 μm), the number of particle layers is insufficient, failing to form an effective nucleation array and reducing cycle capacity retention. When the coating is too thick, although cycle stability is further improved, the ion transport path lengthens, energy density decreases, and material costs increase. Therefore, this invention achieves the optimal balance between energy density and cycle life.
[0018] The spherical resin hard carbon of this invention has a significantly lower BET specific surface area than existing pulverized hard carbon and commercially available wide-distribution hard carbon products. By reducing the specific surface area of the coating through narrow-particle-size spherical hard carbon, the low specific surface area effectively suppresses the side reactions at the interface between the electrolyte and the active material, reduces the continuous growth of the solid electrolyte interphase (SEI) film, and thus significantly improves the first coulombic efficiency and cycle life of the battery.
[0019] Furthermore, the method for preparing the negative electrode sheet of the present invention adopts a general process of slurry mixing, coating and rolling throughout the entire process. It does not require special equipment such as plasma treatment, etching or vacuum deposition, and can achieve large-scale production without special modifications. It is fully compatible with existing sodium electrode sheet production lines and has good prospects for industrial application. Detailed Implementation
[0020] To make the technical solutions and advantages of the present invention clearer, the present invention will be clearly and completely described below in conjunction with specific embodiments. Without departing from the scope or spirit of the present invention, those skilled in the art can make various improvements and changes to the specific embodiments of the present invention, which will be obvious to those skilled in the art.
[0021] The raw materials or equipment involved in this invention are sourced as follows: Phenol from Yanshan Petrochemical; Formaldehyde aqueous solution from Jinan Shengquan, with a mass fraction of 37%; Polyvinyl alcohol (PVA-1788) from Anhui Wanwei; Sodium carboxymethyl cellulose (CMC2200) from Daicel, Japan; Conductive carbon black (Super P Li) from Temico, Switzerland; Aluminum alloy foil (1070 aluminum alloy foil); Modified styrene-butadiene rubber (SBR) emulsion, with a solid content of 40-50%, from Zeon, Japan; and Sodium nickel iron manganese oxide (NFM, NaNi) cathode material. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2) from German nanotechnology, median particle size D 50The thickness is 5.0 μm. The polyvinylidene fluoride (PVDF) is catalog number HSV900 and sourced from Arkema. The electrolyte is a propylene carbonate (PC) solution containing 1.0 M sodium hexafluorophosphate (NaPF6) and 5 vol% fluoroethylene carbonate (FEC), sourced from Suzhou Duoduo Chemical. The doctor blade cast coating machine is model MSK-AFA-III, and the roller press is model MSK-HRP-01, sourced from Hefei Kejing.
[0022] Example 1 This embodiment provides a spherical resin-coated hard carbon negative electrode sheet, the preparation method of which includes the following steps: Step 1: Preparation of spherical resin hard carbon Emulsion polymerization: 100g of phenol, 150g of 37% formaldehyde aqueous solution, 3g of polyvinyl alcohol, and 800mL of deionized water were added to a reactor. The mixture was stirred at 300rpm and heated to 85℃ for 4h. After the reaction, the solid was separated by centrifugation, washed three times with deionized water, and then dried at 80℃ for 12h to obtain phenolic resin microspheres.
[0023] Carbonization: The above phenolic resin microspheres were placed in a tube furnace, and the temperature was raised to 1200℃ at a heating rate of 2℃ / min under the protective atmosphere of nitrogen with a purity of 99.999% (gas flow rate 200mL / min). The temperature was held for 3 hours for carbonization treatment, and then naturally cooled to room temperature to obtain spherical resin hard carbon.
[0024] The basic physical properties of the spherical resin hard carbon obtained above were determined as follows: The particle size of the spherical resin hard carbon was measured using a Malvern Mastersizer 3000 laser particle size analyzer, and it showed a certain distribution range with a median particle size (D). 50 The minimum particle size is 2.5 μm, and the minimum particle size (D) is 2.5 μm. min The particle size is 1.5 μm, and the maximum particle size (D) is 1.5 μm. max The specific surface area (BET) of the spherical resin hard carbon was 7.0 μm. Using a Micron ASAP 2460 surface area analyzer, the BET specific surface area of the spherical resin hard carbon was determined to be 2.8 m². 2 / g. The tap density of the spherical resin hard carbon, measured using a tap density meter, was 0.95 g / cm³. 3 The interlayer spacing (d) of spherical resin hard carbon was measured using a Rigaku SmartLab XRD diffractometer. 002 The wavelength is 0.378 nm.
[0025] Step 2: Preparation of the negative electrode sheet Slurry preparation: Dissolve 2 parts by weight of sodium carboxymethyl cellulose (CMC) in 98 parts by weight of deionized water to prepare a 2 wt% adhesive solution. Add 94 parts of the spherical resin hard carbon obtained in step one and 2 parts of conductive carbon black to the above adhesive solution, place it in a planetary mixer, and stir for 30 minutes at a revolution speed of 2000 rpm and a rotation speed of 800 rpm. Then add 4 parts of modified styrene-butadiene rubber (SBR) emulsion to the planetary mixer, stir for 15 minutes at a revolution speed of 1500 rpm, and finally add deionized water to adjust the slurry solid content to 35%, continue stirring for 10 minutes until homogeneous, and vacuum degas for 5 minutes to obtain the coating slurry.
[0026] Coating: Using a 12μm thick aluminum alloy foil as a substrate, the above coating slurry is coated on both sides of the aluminum alloy foil using a doctor blade casting coating machine. The coating speed is 3.0m / min and the coating gap (wet film thickness) is 48μm to obtain the coated electrode.
[0027] Drying: The coated electrode sheets are dried in five stages of hot air drying, with drying temperatures of 60℃, 80℃, 100℃, 120℃ and 100℃ respectively, and a total drying time of 4 minutes. The drying time for each of the five stages is the same.
[0028] Roll pressing: At room temperature (25±5℃), the dried electrode sheets were rolled using a roller press with a linear pressure of 130 N / mm. The coating thickness after rolling was 20 μm, and the compaction density was 0.82 g / cm³. 3 Thus, the spherical resin hard carbon coated negative electrode sheet of this embodiment is obtained.
[0029] This embodiment also provides a sodium-ion full battery with a low negative electrode, which is a stacked soft-pack battery with a specification of 20Ah assembled from the negative electrode sheet prepared in this embodiment. Specifically, the positive electrode sheet, negative electrode sheet, electrolyte, separator and shell are assembled into a battery, and then the battery is obtained through liquid injection and formation processes.
[0030] The parameters of each main component are as follows: The current collector of the positive electrode is a 12μm thick aluminum alloy foil, and the active material layer is a sodium nickel iron manganese oxide (NFM) positive electrode material layer, which is prepared by mixing NFM, conductive carbon black, and polyvinylidene fluoride (PVDF) in a mass ratio of 93:3:4 and dissolving them in N-methylpyrrolidone (NMP) to prepare a positive electrode slurry with a solid content of 60wt%. The positive electrode slurry is then coated on both sides of the aluminum alloy foil surface, with a coating density of 18.0 mg / cm³. 2, followed by drying, rolling, and slitting to obtain a positive electrode sheet. The separator is a Celgard 2500 single-layer polypropylene separator, and the number of stacked layers is 21. The electrolyte is 1.0M NaPF6 / PC+FEC (5vol%), and the electrolyte injection amount is 4.5g / Ah. Formation procedure: charge at a constant current of 0.05C to 3.95V, stand still for 5min, then discharge at 0.05C to 2.0V, and perform the charge-discharge cycle process for 2 weeks.
[0031] The positive electrode areal capacity of the anode-less sodium-ion full cell in this example (calculated based on the NFM specific capacity of 190mAh / g) is 3.42mAh / cm 2 , and the hard carbon areal capacity is 0.63mAh / cm 2 , with an N / P ratio (hard carbon areal capacity / positive electrode areal capacity) of 0.18.
[0032] Example 2 This example provides a spherical resin hard carbon coated negative electrode sheet, and the only difference between its preparation method and that of Example 1 is that in step 2, the coating gap is adjusted to 30μm, the linear pressure of the roller press is adjusted to 80N / mm, the coating thickness after rolling is 12μm, and other conditions remain unchanged.
[0033] This example further provides an anode-less sodium-ion full cell, which uses the negative electrode sheet of this example to replace the negative electrode sheet of Example 1, with the remaining parameters the same as those of Example 1. The positive electrode areal capacity of the anode-less sodium-ion full cell in this example is 3.42mAh / cm 2 , and the hard carbon areal capacity is 0.38mAh / cm 2 , with an N / P ratio (hard carbon areal capacity / positive electrode areal capacity) of 0.11.
[0034] Example 3 This example provides a spherical resin hard carbon coated negative electrode sheet, and the only difference between its preparation method and that of Example 1 is that in step 2, the coating gap is adjusted to 70μm, the linear pressure of the roller press is adjusted to 200N / mm, the coating thickness after rolling is 30μm, and other conditions remain unchanged.
[0035] This example further provides an anode-less sodium-ion full cell, which uses the negative electrode sheet of this example to replace the negative electrode sheet of Example 1, with the remaining parameters the same as those of Example 1. The positive electrode areal capacity of the anode-less sodium-ion full cell in this example is 3.42mAh / cm 2 , and the hard carbon areal capacity is 0.95mAh / cm 2 , with an N / P ratio (hard carbon areal capacity / positive electrode areal capacity) of 0.28.
[0036] Example 4 This embodiment provides a spherical resin hard carbon coated negative electrode sheet. The only difference between this preparation method and that of Example 1 is that in step two, the coating gap is adjusted to 92 μm, the linear pressure of the roller press is adjusted to 270 N / mm, and the coating thickness after roller pressing is 40 μm, while other conditions remain unchanged.
[0037] This embodiment also provides a sodium-ion full battery with a low negative electrode, which uses the negative electrode sheet of this embodiment instead of the negative electrode sheet of Embodiment 1, while the other parameters are the same as those of Embodiment 1. The positive electrode surface capacity of the sodium-ion full battery with a low negative electrode in this embodiment is 3.42 mAh / cm². 2 The hard carbon surface capacity is 1.26mAh / cm². 2 The N / P ratio (hard carbon surface capacity / positive electrode surface capacity) is 0.37.
[0038] Example 5 This embodiment provides a spherical resin hard carbon coated negative electrode, the only difference between its preparation method and that of Example 1 is that in step one, the stirring speed of the emulsion polymerization is adjusted to 500 rpm, and the resulting spherical resin hard carbon has a D... 50 It is 2.0 μm, D min It is 1.1 μm, D max Its thickness is 5.8 μm, and its BET specific surface area is 3.1 m². 2 / g, other conditions remain unchanged.
[0039] This embodiment also provides a sodium-ion full battery with a low negative electrode, which uses the negative electrode sheet of this embodiment instead of the negative electrode sheet of embodiment 1, and the other parameters are the same as those of embodiment 1.
[0040] Example 6 This embodiment provides a spherical resin hard carbon coated negative electrode, the only difference between its preparation method and that of Example 1 is that in step one, the stirring speed of the emulsion polymerization is adjusted to 200 rpm, and the resulting spherical resin hard carbon has a D 50 It is 3.0 μm, D min It is 1.8μm, D max Its thickness is 7.8 μm, and its BET specific surface area is 2.5 m². 2 / g, other conditions remain unchanged.
[0041] This embodiment also provides a sodium-ion full battery with a low negative electrode, which uses the negative electrode sheet of this embodiment instead of the negative electrode sheet of embodiment 1, and the other parameters are the same as those of embodiment 1.
[0042] Example 7 This embodiment provides a spherical resin hard carbon coated negative electrode, the only difference between its preparation method and that of Embodiment 1 is that in step one, the carbonization temperature is adjusted to 1300℃, and the resulting spherical resin hard carbon has a D 50 It is 3.0 μm, D min It is 2.1 μm, Dmax Its thickness is 7.8 μm, and its BET specific surface area is 1.9 m². 2 / g, other conditions remain unchanged.
[0043] This embodiment also provides a sodium-ion full battery with a low negative electrode, which uses the negative electrode sheet of this embodiment instead of the negative electrode sheet of embodiment 1, and the other parameters are the same as those of embodiment 1.
[0044] Comparative Example 1 The comparative example provides a negative electrode sheet, which is a 12μm thick aluminum alloy foil with no coating on the surface (bare aluminum foil).
[0045] Comparative Example 2 This comparative example provides a negative electrode sheet whose preparation method differs from Example 1 only in that the preparation process of spherical resin hard carbon in step one is omitted, and in step two, an equal mass fraction of commercially available hard carbon material (model H35-R4) is used to replace the spherical resin hard carbon for the preparation of the negative electrode sheet, while other conditions remain unchanged. The D of this commercially available hard carbon material... 50 Its thickness is 5.3 μm, and its BET specific surface area is 6.2 m². 2 / g, the coating thickness after roll pressing is 20μm.
[0046] Comparative Example 3 This comparative example provides a negative electrode sheet whose preparation method differs from that of Example 1 only in that: in step two, the linear pressure of the roller press is adjusted to 540 N / mm, and the coating thickness after roller pressing is 80 μm (the thickness of a traditional negative electrode), while other conditions remain unchanged.
[0047] Comparative Example 4 This comparative example provides a negative electrode sheet whose preparation method differs from Example 1 only in that: in step two, the preparation process of spherical resin hard carbon in step one is omitted; and in step two, an equal mass proportion of pulverized non-spherical hard carbon is used instead of spherical resin hard carbon to prepare the negative electrode sheet, while other conditions remain unchanged. This pulverized non-spherical hard carbon is obtained through a pulverization process. 50 It is 2.5μm, D min It is 0.6μm, D max Its thickness is 18.2 μm, and its BET specific surface area is 9.3 m². 2 / g, with an irregular polyhedral morphology, and a coating thickness of 20μm after roll pressing.
[0048] Comparative Example 5 This comparative example provides a negative electrode sheet whose preparation method differs from that of Example 1 only in that: in step two, the coating gap is adjusted to 15μm, the linear pressure of the roller press is adjusted to 30N / mm, and the coating thickness after roller pressing is 5μm, while other conditions remain unchanged.
[0049] Comparative Example 6 This comparative example provides a negative electrode sheet whose preparation method differs from that of Example 1 only in that: in step two, the amount of spherical resin hard carbon is adjusted to 90 parts, and the amount of conductive carbon black is adjusted to 6 parts, while other conditions remain unchanged.
[0050] Comparative Example 7 This comparative example provides a negative electrode sheet whose preparation method differs from that of Example 1 only in that: in step two, the rolling process is omitted, that is, the electrode sheet is used directly after coating and drying without rolling, the coating thickness is 30μm, and other conditions remain unchanged.
[0051] Comparative Example 8 This comparative example provides a negative electrode sheet whose preparation method differs from Example 1 only in that: in step two, a PVDF / NMP slurry system is used instead of the CMC / SBR aqueous slurry system, with a formulation of spherical resin hard carbon, conductive carbon black, and polyvinylidene fluoride in a mass ratio of 94:2:4. The slurry preparation process is specifically adjusted as follows: by mass, 4 parts of polyvinylidene fluoride (PVDF) are dissolved in N-methyl-2-pyrrolidone (NMP) and stirred until completely dissolved into a transparent gel to obtain a slurry. Another 94 parts of the spherical resin hard carbon obtained in step one and 4 parts of conductive carbon black are added to the above slurry and placed in a planetary mixer. The mixture is stirred for 120 minutes at a revolution speed of 2000 rpm and a rotation speed of 800 rpm. Finally, NMP is added to adjust the slurry solid content to 35%, and stirring is continued for 10 minutes until homogeneous. Vacuum degassing is then performed for 5 minutes to obtain the coating slurry, with other conditions remaining unchanged.
[0052] Test Example 1: Half-Battery Performance Test The negative electrode sheets prepared in Examples 1-7 and Comparative Examples 1-8 were cut into Φ14mm discs. Using a sodium metal sheet (Sigma-Aldrich, 99.8%) as the counter electrode, Whatman GF / D glass fiber as the separator, and 1.0M NaPF6 / PC+FEC (5 vol%) as the electrolyte, they were assembled into CR2032 coin cells in an inert atmosphere glove box. Test parameters included: initial coulombic efficiency, capacity retention after 100 and 200 cycles, and overpotential.
[0053] The testing process is as follows: Initial coulombic efficiency: After the assembled half-cell was left to stand for 12 hours, it was tested in a constant temperature chamber (25±1℃). First, constant current and constant voltage discharge (sodium insertion) was performed at a current density of 0.05C. The constant current was first discharged to 0.05V, and then constant voltage discharge was performed at 0.05V until the current dropped to 0.01C to ensure that the hard carbon sodium storage sites were fully sodiumized. Then, constant current charging (sodium removal) was performed at a current density of 0.05C to 1.5V. The initial charge capacity and initial discharge capacity were recorded, and the initial coulombic efficiency was calculated according to the following formula: Initial coulombic efficiency = Initial charge capacity / Initial discharge capacity × 100%.
[0054] Cycling performance: After completing the initial charge-discharge process in step 1) above, the sodium-ion battery was subjected to constant current charge-discharge cycle testing at a current density of 0.5C within a voltage window of 0.05V~1.5V. The discharge capacity was recorded after the 100th and 200th cycles. The capacity retention rate was calculated based on the discharge capacity of the first cycle at 0.5C after activation. The capacity retention rate (%) = (Discharge capacity in week N / Discharge capacity in week 1) × 100%.
[0055] Overpotential: Select the charge-discharge curve of the 50th cycle, and read the median discharge voltage (voltage when the discharge capacity reaches half) and the median charge voltage (voltage when the charge capacity reaches half). Calculate the overpotential using the following formula: Overpotential = (Median charge voltage - Median discharge voltage) / 2. The lower the overpotential, the smaller the electrochemical polarization, which is more conducive to the rapid insertion and extraction of sodium ions.
[0056] Table 1 shows the performance test results of the half-cells assembled from the negative electrode sheets prepared in Examples 1-7 and Comparative Examples 1-8.
[0057] Table 1. Performance test results of half-cells assembled with negative electrode plates
[0058] As shown in Table 1, the sodium-ion batteries prepared with the negative electrode sheets of the present invention exhibit excellent initial coulombic efficiency (90.1%~92.8%), 200-cycle capacity retention (77.2%~86.5%), and overpotential (13.7mV~20.1mV), confirming the effectiveness of the present invention. Specifically, a comparison of Examples 1-4 shows that when the thickness of the spherical resin hard carbon coating increases from 12μm to 40μm, the initial efficiency slightly decreases (92.3% to 90.1%), the long-cycle capacity retention increases (79.3% to 86.5%), and the overpotential decreases (18.5mV to 13.7mV).
[0059] The test results of Comparative Example 1 show that relying solely on the natural oxide layer on the surface of the aluminum foil for sodium storage results in extremely low capacity and rapid degradation during cycling, proving that the hard carbon coating is a necessary source of active material. Furthermore, a comparison between Example 1 and Comparative Examples 2 and 4 shows that the present invention uses spherical resin hard carbon, which has a spherical morphology and narrow particle size distribution. By reducing surface defects and open channels, it helps to achieve uniform nucleation and suppress electrolyte side reactions, thereby significantly improving the initial coulombic efficiency and long-term cycling stability. The initial efficiency is significantly higher than that of conventional hard carbon (85.3% of Comparative Example 2) and pulverized hard carbon (83.1% of Comparative Example 4). A comparison between Example 1 and Comparative Examples 3 and 5 shows that the present invention uses a thin coating (≤40μm) in synergy with spherical particles. The capacity retention rate after 200 cycles is significantly better than that of excessively thick coatings (81.9% of Comparative Example 3) and excessively thin coatings (58.3% of Comparative Example 5). At the same time, the present invention can effectively save materials compared to the thick coating mode. In addition, the excessive conductive agent in Comparative Example 6, the lack of rolling in Comparative Example 7 resulting in loose contact between particles, and the poor compatibility between the oil-based binder and spherical carbon in Comparative Example 8 all affected the overall performance of the battery.
[0060] Test Example 2: Full Battery Performance Test The negative electrode sheets from Comparative Examples 1-3 were assembled into 20Ah stacked pouch cells using the sodium-ion full cell assembly method described in Example 1, serving as test samples for sodium-ion full cells. The positive electrode was an NFM positive electrode, and the separator was a Celgard 2500 single-layer polypropylene membrane with 21 stacked layers. The electrolyte was 1.0M NaPF6 / PC+FEC (5 vol%), with an injection volume of 4.5 g / Ah. Formation regime: After the assembled cells were allowed to stand for 12 hours, they were charged at a constant current of 0.05C to 3.95V, allowed to stand for 5 minutes, and then discharged at a constant current of 0.05C to 2.0V. This cycle was repeated for 2 weeks to complete the formation.
[0061] The initial coulombic efficiency and battery energy density are calculated using the charge and discharge data from the first cycle of formation, according to the following formula: Initial coulombic efficiency (%) = (initial charge capacity / initial discharge capacity) × 100%.
[0062] Battery energy density (Wh / kg) = (Discharge capacity in week 1 × Average discharge voltage) / Total battery mass. Here, total battery mass refers to the total mass of the battery cells; the average discharge voltage is obtained by integrating the discharge curve.
[0063] Cyclic performance test: After formation, the sodium-ion battery was charged at a constant current of 0.5C to 3.95V, then switched to constant voltage charging until the current dropped to 0.05C; after resting for 10 minutes, it was discharged at a constant current of 0.5C to 2.0V, and then rested for 10 minutes. This charge-discharge cycle test was repeated. The discharge capacity at the 500th and 1000th cycles of 0.5C was recorded and calculated using the following formula: Capacity retention (%) = (Discharge capacity at week N / Discharge capacity at week 1) × 100%.
[0064] Table 2 shows the performance test results of sodium-ion full cells assembled from the negative electrode sheets prepared in Example 1 and Comparative Examples 1-3.
[0065] Table 2. Performance test results of sodium-ion full cells assembled with negative electrode sheets
[0066] As shown in Table 2, compared to Comparative Examples 1-3, the sodium-ion full cells prepared with the negative electrode sheets of this invention exhibit superior energy density, initial coulombic efficiency, and long-term cycle stability. While Comparative Example 1, using bare aluminum foil, contributes some sodium storage capacity, it suffers from severe side reactions and extremely rapid cycle decay, rendering it impractical. Comparative Example 2 shows poor cycle performance, indicating that commercially available hard carbon exhibits excessively rapid capacity decay under ultrathin coatings. Comparative Example 3 has a low energy density due to its excessively thick negative electrode coating, which significantly increases the total battery mass, leading to a substantial decrease in energy density. Therefore, this invention, through optimization with spherical hard carbon and the use of an ultrathin 20μm hard carbon coating, provides an effective array of nucleation sites, effectively improving the battery's cycle life and energy density, making it suitable as a negative electrode solution for high-energy-density sodium batteries.
[0067] In summary, the negative electrode sheet of the present invention is a sodium-ion battery negative electrode sheet characterized by a spherical resin hard carbon ultrathin coating. It adopts a four-in-one design of low negative electrode, spherical carbon, thin coating, and roll forming. It constructs a uniform nucleation site array through narrow-diameter spherical particles, taking into account the dual functions of hard carbon sodium storage and sodium metal deposition. It achieves the best balance between energy density (≥160Wh / kg), cycle life (1000-cycle retention rate ≥79%), and kinetic performance (overpotential ≤20mV). Moreover, the preparation process is fully compatible with existing production lines, and it has the advantages of high performance, low cost, and easy mass production. It has good industrial application prospects in the field of sodium-ion battery negative electrode preparation.
[0068] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art can make various improvements and modifications without departing from the spirit and principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A spherical resin-coated hard carbon negative electrode, characterized in that, The system includes a current collector and an active material layer loaded on the surface of the current collector; the active material layer comprises spherical resin hard carbon; the thickness of the active material layer is 12~40μm; the spherical resin hard carbon is obtained by carbonization treatment of phenolic resin microspheres, with a median particle size D. 50 The thickness is 2.0~3.0μm.
2. The spherical resin hard carbon coated negative electrode sheet according to claim 1, characterized in that, The current collector is an aluminum alloy foil or aluminum foil; the thickness of the current collector is 8~15μm; the maximum particle size D of the spherical resin hard carbon is... max The particle size ranges from 5.8 to 7.8 μm, with a minimum particle size D. min Its thickness is 1.1~1.8μm, and its BET specific surface area is 1.9~3.1m². 2 / g; the phenolic resin microspheres are prepared by emulsion polymerization.
3. The spherical resin hard carbon coated negative electrode sheet according to claim 1, characterized in that, The raw materials for preparing the active material layer include, by mass parts: 90-96 parts of spherical hard carbon resin, 1-4 parts of conductive carbon black, 1-4 parts of sodium carboxymethyl cellulose, and 2-5 parts of styrene-butadiene rubber emulsion.
4. The spherical resin hard carbon coated negative electrode sheet according to claim 1, characterized in that, The method for preparing the spherical resin hard carbon includes: heating phenol, formaldehyde aqueous solution, and polyvinyl alcohol in water under stirring conditions to obtain phenolic resin microspheres; carbonizing the phenolic resin microspheres in a protective atmosphere to obtain the spherical resin hard carbon; the mass ratio of phenol, formaldehyde aqueous solution, and polyvinyl alcohol is (80~120):(120~200):(2~5); the stirring speed is 200~500 rpm; the heating reaction temperature is 70~90℃ and the time is 2~8h; the carbonization treatment temperature is 1100~1300℃ and the time is 2~5h.
5. A method for preparing a spherical resin hard carbon coated negative electrode sheet as described in any one of claims 1 to 4, characterized in that, Includes the following steps: Spherical resin hard carbon, conductive carbon black, sodium carboxymethyl cellulose, styrene-butadiene rubber emulsion, and solvent are mixed evenly to obtain a coating slurry. The coating slurry is then coated onto the surface of the current collector, dried, and rolled to obtain the spherical resin hard carbon coated negative electrode sheet. The amount of spherical resin hard carbon used is 90-96 parts by mass, the amount of conductive carbon black is 1-4 parts, the amount of sodium carboxymethyl cellulose is 1-4 parts, and the amount of styrene-butadiene rubber emulsion is 2-5 parts.
6. The method for preparing the spherical resin hard carbon coated negative electrode sheet according to claim 5, characterized in that, The solvent is water; the solid content of the coating slurry is 30-40%.
7. The method for preparing the spherical resin hard carbon coated negative electrode sheet according to claim 5, characterized in that, The preparation steps of the coating slurry specifically include: first, dissolving sodium carboxymethyl cellulose in a solvent to prepare a glue solution; adding spherical resin hard carbon and conductive carbon black to the glue solution and stirring; finally adding styrene-butadiene rubber emulsion and stirring; then adding solvent and adjusting the solid content; finally stirring and degassing to obtain the coating slurry.
8. The method for preparing the spherical resin hard carbon coated negative electrode sheet according to claim 5, characterized in that, The coating speed is 1.0~5.0m / min, and the coating gap is 30~92μm; the drying adopts multi-stage hot air drying, the drying temperature is 60~120℃, and the total drying time is 3~6min; the rolling is carried out at room temperature, and the rolling linear pressure is 80~270N / mm.
9. A sodium-ion battery with a low negative electrode, comprising a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte, characterized in that, The negative electrode sheet is the negative electrode sheet as described in any one of claims 1 to 4, or the negative electrode sheet prepared by the preparation method described in any one of claims 5 to 8.
10. The sodium-ion battery with fewer negative electrodes according to claim 9, characterized in that, The positive electrode sheet includes a positive current collector and a positive active material layer loaded on the surface of the positive current collector; the raw materials for preparing the positive active material layer include sodium nickel iron manganese oxide, conductive carbon black and binder; the non-aqueous electrolyte contains sodium salt, non-aqueous organic solvent and fluoroethylene carbonate; the separator is a polypropylene or polyethylene separator.